2011
DOI: 10.1017/s0033291711000092
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of salivary cortisol and α-amylase responses to psychosocial stress in anorexia nervosa but not in bulimia nervosa

Abstract: These findings demonstrate, for the first time, the occurrence of an asymmetry between the HPA axis and SNS components of the stress response in the acute phase of AN but not in BN. The pathophysiological significance of this asymmetry remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
42
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 34 publications
13
42
2
Order By: Relevance
“…The present results also implicate differences in HPA axis activation. The only previous study to examine both sympathetic and HPA axis activation found blunted cortisol stress reactivity in bulimic patients, but blunted a-amylase reactivity in patients with anorexia nervosa, suggesting some specificity in the two branches of the stress effector system (Monteleone et al, 2011). Others have proposed that sympathetic and HPA activation can be dissociated in some circumstances (Frankenhaeuser, 1982;Dickerson and Kemeny, 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The present results also implicate differences in HPA axis activation. The only previous study to examine both sympathetic and HPA axis activation found blunted cortisol stress reactivity in bulimic patients, but blunted a-amylase reactivity in patients with anorexia nervosa, suggesting some specificity in the two branches of the stress effector system (Monteleone et al, 2011). Others have proposed that sympathetic and HPA activation can be dissociated in some circumstances (Frankenhaeuser, 1982;Dickerson and Kemeny, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…It is important to determine whether dysregulation of the stress response is characteristic of both branches, of the stress effector system: hypothalamic-pituitary-adrenal (HPA) axis and sympathetic nervous system. The one study, to date, to examine this issue measured cortisol and a-amylase, considered a marker of sympathetic nervous system activation (Chatterton et al, 1996), to a standard laboratory stress exposure (Monteleone et al, 2011) in women with anorexia nervosa and bulimia. Relative to those with anorexia nervosa, women with bulimia showed blunted cortisol reactivity, whereas women with anorexia nervosa showed blunted a-amylase reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The AUC G cortisol outcome measure was selected a priori as our primary end-point. Based on previous investigations in other pathological conditions with sample sizes of 10-14 participants per group (Chopra et al 2009;Monteleone et al 2011), our study was powered to detect a 1.5-fold group difference on AUC G cortisol levels with an expected large effect size d = 0.80 (Cohen, 1988), with 50.80 power and α = 0.05. Data are presented as mean ± standard error of the mean (S.E.M.).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently proposed that ghrelin may mediate the rewarding aspects of eating that are separated from eating-associated body weight homeostasis [36] and, therefore, its rise after stress exposure could be involved in stress-induced feeding where the ingestion of food is aimed at reducing negative emotions by increasing food-derived feelings of pleasure. Therefore, since in our BN patients the ghrelin secretion in response to TSST was amplified, we could speculate that when BN patients are in conditions of negative mood states, the psychological distress may induce an exaggerated ghrelin secretion which could constitute a strong signal of hunger and/or urge to eat, thereby prompting binge eating.…”
Section: Discussionmentioning
confidence: 99%